2019
DOI: 10.1111/febs.15028
|View full text |Cite
|
Sign up to set email alerts
|

The influence of microenvironment on tumor immunotherapy

Abstract: Tumor immunotherapy has achieved remarkable efficacy, with immune‐checkpoint inhibitors as especially promising candidates for cancer therapy. However, some issues caused by immunotherapy have raised attention, such as limited efficacy for some patients, narrow antineoplastic spectrum, and adverse reactions, suggesting that using regulators of tumor immune response may prove to be more complicated than anticipated. Current evidence indicates that different factors collectively constituting the unique tumor mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 146 publications
(166 reference statements)
0
74
0
Order By: Relevance
“…By normalizing the CCTF and CAM expression to different days during tumor expansion, it becomes apparent that at any given time point, there are complex processes at work influencing the status (i.e., hot or cold) of the TME [51]. The communication of the tumor cells with the TME includes the autocrine/paracrine release of CCTFs, proteases, bioactive molecules, extracellular matrix (ECM) remodeling, cancer-associated fibroblast (CAF), immune cell populations, exosomes, areas of hypoxia, acidosis, nutritional demands, genetic drift, and enhanced anti-apoptotic signaling along with vasculogenesis, which will allow for the tumor expansion in the absence of treatment [51][52][53][54]. The natural history changes in CCTFs and CAMs in both B16 and 4T1 tumors revealed that with growth progression, there was a shift toward an immunosuppressive or cold TME.…”
Section: Discussionmentioning
confidence: 99%
“…By normalizing the CCTF and CAM expression to different days during tumor expansion, it becomes apparent that at any given time point, there are complex processes at work influencing the status (i.e., hot or cold) of the TME [51]. The communication of the tumor cells with the TME includes the autocrine/paracrine release of CCTFs, proteases, bioactive molecules, extracellular matrix (ECM) remodeling, cancer-associated fibroblast (CAF), immune cell populations, exosomes, areas of hypoxia, acidosis, nutritional demands, genetic drift, and enhanced anti-apoptotic signaling along with vasculogenesis, which will allow for the tumor expansion in the absence of treatment [51][52][53][54]. The natural history changes in CCTFs and CAMs in both B16 and 4T1 tumors revealed that with growth progression, there was a shift toward an immunosuppressive or cold TME.…”
Section: Discussionmentioning
confidence: 99%
“…However, one drawback of immunotherapy is its unsatisfactory effects on deep solid tumors [ 14 ]. Consequently, to improve cancer immunotherapy, there is an urgent demand for novel strategies to reverse and remodel immunosuppressive microenvironments [ 15 ]. The development of nanomedicine has provided a novel approach to enhance immunotherapeutic efficacy and minimize adverse toxicities [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, immuno-supportive phenotypes, which exhibit greater baseline antitumor immunity and improved immunotherapy response, have been linked to the presence of TILs and elevated expression of programmed death-ligand 1 (PD-L1) on tumor-associated immune cells. In contrast, immuno-suppressive phenotypes have been linked to the presence of tumor-associated macrophages and fibroblasts, as well as reduced PD-L1 expression [28][29][30] . HIF-based approaches have the potential to provide an interpretable window into the composition and spatial architecture of the TME in a manner complementary to conventional genomic approaches.…”
Section: Introductionmentioning
confidence: 99%